A STUDY ON THE ABILITY OF THE ELEVENTH GRADE STUDENTS OF SMAN 5 PEKANBARU IN WRITING NARRATIVE PARAGRAPHS - Putri Anila Husein Anila Husein; Rumiri Aruan Rumiri Aruan; Eliwarti Eliwarti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This descriptive study aimed to find out the ability of the eleventh grade students of SMAN 5 Pekanbaru in writing narrative paragraphs. The population of the research was the eleventh grade students of SMAN 5 Pekanbaru, while the sample was 36 students of XI IPA 1 which was decided by using cluster sampling technique. The instrument used in this study was a written test. The students’ score were graded by three raters and analyzed by using Harris’ scoring system which concerned with five aspects of writing, such as content, form, grammar, style, and mechanics. The findings showed that there were 7 students (19%) in excellent level, 18 students (50%) in good level, 9 students (25%) in average level, and 2 students (6%) in poor level. It was also found that the students’ ability in terms of content was the highest among the other aspects, with the average score of 75,69, while grammar was the lowest one, with the average score of 60. The students’ average score for each aspect of writing was in good level. Based on the result obtained, it can be inferred that the eleventh grade students of SMAN 5 Pekanbaru were able to write narrative paragraphs and their level of ability was in good level with the average score of 66. This study recommended the students to pay more attention in terms of grammar and style since the score of these two aspects were low. Then, the teacher should pay more attention,too, on these two aspects as well as the other aspects: mechanics, form, and content. Further researchers can focus on studying each aspect in details.Keywords: Ability, writing, narrative paragraphs.